EFEKTIVITAS PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH DAN SELF-REGULATED LEARNING MAHASISWA - Arifin, Nurdin (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
The purpose of this study is to find out the effectiveness of online learning students using SPADA in review of problem-solving and self-regulated learning skills in linear program materials algebra courses. This research was conducted at Widya Gama University in semester 5A class in 2020. This study is an experimental study with method 1) One-Shot Case Study, to obtain data on student problem-solving skills and 2) One-Group Pretest-Posttest Design, to obtain data on student self-regulated learning. Based on the results of the study, 1) online learning with SPADA on linear program materials is effectively reviewed from the problem-solving ability of PGSD students of Widya Gama Mahakam Samarinda University and 2) online learning with SPADA on linear program materials effectively reviewed from self-regulated learning of PGSD students of Widya Gama Mahakam Samarinda University. Researchers will be able to explore how mediation factors (such as motivation) work with self-regulated learning to improve our understanding of the influence of student self-regulation on academic success in online learning in life.